Konsep Targib wa Tarhib dalam Naskah Arba’in Madyani - Agil Muhammad (Institut Islam Nahdlatul Ulama Temanggung, 2019)
There are many religious manuscripts that are scattered and have not been studied extensively and deeply. One of the manuscripts is the Arba‘in Madyani manuscript which contained 49 hadiths and was written in 1267 H / 1851 AD by Kiai Abu Ishaq Madyani. This study aims to describe the text and to analyze the concept of the Targib wa Tarhib in the Arba‘in Madyani text. This research uses descriptive methods combined with modern philology methods. The data source in this research is a copy of Arba‘in Madyani manuscript which is stored in the house of the heirs located in Nguruan, Soko, Tuban. East Java. Data is analyzed by the philology approach that is integrated with the hadith science approach. The research of hadith quality in this book uses the rules of hadith validity, both in terms of the sanad and matan. The results of this study indicate that the Arba‘in Madyani manuscript is a single text and the condition of the Arba‘in Madyani manuscript is still maintained, clear and easy to read writing written in Arabic. The concept of Targib wa Tarhib in the Arba‘in Madyani book consists of several parts, namely solicitation and threat in prayer and prayer in congregation, studying, glorifying mosques, daily ethics, generosity, the virtue of recitation of dhikr, and marriage. The concepts of the Targib wa Tarhib adapted the conditions around when Kiai Abu Ishaq Madyani still preached in his community with Sufism approach.